ANALISIS PENYELESAIAN KUR MIKRO KREDIT BERMASALAH PADA PT. BRI (PERSERO) TBK. CABANG SAMARINDA UNIT SURYANATA - Heriyanto, Tarigan Irma Norita Ec.Elfreda Aplonia Lau (EKONOMIA, 2016)
Tarigan Irma Norita. The Analysis of Non-Performing Loan Settlement of Micro Credit for Businesses Program of PT. Bank Rakyat Indonesia (Persero) Tbk. Samarinda Branch Unit Suryanata supervised by Ms. ElfredaAplonia Lau and Mr. Heriyanto.Bank is a financial institution which main activities are to accept deposits from the public and to distribute them back in the form of credit. The rapid growth of banks and financial institutions triggered Bank Rakyat Indonesia (BRI) to improve their service. One of BRIâ€™s best services is their quick loan process with flexible terms. This service also has a great risk. The more loans that are granted, the more risk BRI get. The risks may arise into problematic credit and it is called Non-Performing Loan. This research aims to determine and analyze Non-Performing Loan Micro Credit for Businesses at PT. Bank Rakyat Indonesia (Persero) Tbk. Samarinda Branch Unit Suryanata in 2015 that has increased or decreased compared to the period of 2011 to 2015 based on Non-Performing Loans (NPLs) and Loan to Deposit Ratio (LDR). The analytical tool used in this thesis was Banking Financial Ratios Non-performing loans (NPLs) and Loan to Deposit Ratio (LDR). Based on research problem mentioned above about The Analysis of Non-Performing Loan Settlement of Micro Credit for Businesses Program Unit Suryanata, the researcher proposed hypothesis as follows: Non Performing Loan (NPL) at PT. Bank Rakyat Indonesia (Persero) Tbk. Samarinda Branch Unit Suryanata in 2015 decreased and Loan to Deposit Ratio (LDR) PT. Bank Rakyat Indonesia (Persero) Tbk. Samarinda Branch Unit Suryanata 2015 have increased in terms of numbers produced better, compared to non-performing loans (NPLs) and Loan to Deposit Ratio (LDR) in 2011 to 2014 which in 2015 the NPL is about 1.2% below the standard value that has been set by Bank Indonesia at 5% andÂ  LDR is about 55.55